Human rights and the law of human rights: a positive legal regulation of an ontic reality - Nagel, Kalikst (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The author introduces a fundamental distinction between human rights and the law of human rights which is subsequent to these rights. While examining these issues, the author follows M. Piechowiak and his way of understanding human rights. According to Piechowiak, human rights are objectively existing relationships between a human being and a global good, welfare that is due to him/her. Particular aspects of this global good are what we used to call an object of a particular human right. Therefore, human rights have an ontic nature. These relationships have their normative consequences. It may be stated that these relationships ontologically justify that the norms protecting these rights (actually these relationships) stay in force. These relationships and the norms protecting them can be recognized. Notwithstanding what was stated above, human rights shall be proclaimed and the ontic norms protecting them, adequately recognized, shall be positivised, that is, acts of positive law shall introduce these norms into legal systems.